Pengaruh Kecemasan Terhadap Kepatuhan Pengobatan Kanker Payudara - M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar; Milna Sari (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Anxiety is a psychological factor commonly experienced by breast cancer patients and can influence medication adherence. This study aims to analyze the impact of anxiety on medication adherence among breast cancer patients through a meta-analysis of published studies. A systematic search was conducted across electronic databases, including PubMed, Scopus, and PsycINFO, to identify relevant studies published in the last five years. Inclusion criteria encompassed observational and experimental studies measuring anxiety levels and medication adherence in breast cancer patients. A meta-analysis was performed using a random-effects model to compute the effect size. The analysis revealed a significant negative relationship between anxiety levels and adherence to breast cancer treatment (r = -0.38, 95% CI: -0.45 to -0.31, p < 0.001). These findings indicate that patients with higher levels of anxiety are likely to have lower adherence to breast cancer treatment. Consequently, the findings underscore the importance of psychological interventions in reducing patient anxiety and improving medication adherence in breast cancer patients. Finally, the study highlights the need for clinical implications and future research recommendations. The results reinforce the necessity for further research and development in improving treatment outcomes and quality of life for breast cancer patients in the future.